Thrombotic thrombocytopenic purpura: a case report - Drumond,João Paulo N. (2018)
ABSTRACT Thrombocytopenic thrombotic purpura (TTP) is a severe hemorrhagic syndrome characterized by thrombocytopenia, microangiopathic hemolytic anemia and microvascular occlusion, besides the associated symptoms that may or may not be present: fever, neurological and renal impairment. The pathophysiology involves the autoimmune or genetic deficiency of a metalloproteinases activity (ADAMTS-13), responsible for the von Willebrand Factor cleavage. The treatment is based on plasmapheresis; and in acute or recurrent cases, corticosteroids and immunosuppressants are associated. In this article, we will discuss a case report about this disease, initially treated in the Emergency Room and followed in the Intensive Care Unit of a public reference hospital in São Paulo city, Brazil. All clinical diagnostic criteria were completely filled, facilitating the therapeutic approach of the patient. The report evidences that rapid intervention when made early diagnosis evolves with a good prognosis, and this pathology must be present as a differential diagnosis in the medical routine.